Sessiia Verkhovnogo Soveta Rossiiskoi Federatsii . Sessiia Verkhovnogo Soveta Rossiiskoi Federatsii . Session of the Supreme Soviet of the Russian Federation . Сессия Верховного Совета Российской Федерации - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the Constitutional Court's conclusions regarding President Boris Yeltsin's actions and decisions linked to his address to Russian citizens on 20 March 1993. Featured in the program: Rudkin, IUrii (Secretary of the Constitutional Court of Russia) Обсуждение заключения Конституционного суда РФ о соответствии конституции РФ действий и решений президента Бориса Ельцина, связанных с его обращением к гражданам России 20 марта 1993 года. В программе участвуют: Рудкин, Юрий (Секретарь Конституционного суда России)